2015
DOI: 10.5121/ijdkp.2015.5601
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Customer's Evaluations Through Mining Airline Reviews

Abstract: Data mining can be evaluated as a strategic tool to determine the customer profiles in order to learn customer expectations and requirements. Airline customers have different characteristics and if passenger reviews about their trip experiences are correctly analyzed, companies can increase customer satisfaction by improving provided services. In this study, we investigate customer review data for in-flight services of airline companies and draw customer models with respect to such data. In this sense, we appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…To that end, we perform clustering and cluster labeling of the review content in order to identify topics which are discussed in reviews. In contrast to [19], we do not cluster the content with the commonly used k-means approach but rather using Suffix Tree Clustering (STC) [21], an approach that focuses on the problem of cluster labeling. We justify our choice since this clustering technique merges base clusters with high textual overlaps and was shown to outperform group average agglomerative hierarchical clustering, k-means, buckshot, fractionation and single-pass algorithms [21,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To that end, we perform clustering and cluster labeling of the review content in order to identify topics which are discussed in reviews. In contrast to [19], we do not cluster the content with the commonly used k-means approach but rather using Suffix Tree Clustering (STC) [21], an approach that focuses on the problem of cluster labeling. We justify our choice since this clustering technique merges base clusters with high textual overlaps and was shown to outperform group average agglomerative hierarchical clustering, k-means, buckshot, fractionation and single-pass algorithms [21,14].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this data may be a valuable source for researchers that aim at better understanding the factors that contribute to user satisfaction. One recent work going into that direction is the one described in [19], in which the authors mined review data about airlines' inflight services from the Skytrax portal. By grouping travelers via feature-based and clustering-based modelling, the authors showed that inferences can be captured to explain how travelers evaluate in-flight services.…”
Section: Related Workmentioning
confidence: 99%
“…He applied eight machine learning models for patient complaint classification using the explored rules to achieve significantly higher results as compared with basic unigram features using the same models. Yakut et al [9] explored customer review data for in-flight services of airline companies and draw customer models with respect to such data. He applied two modelling techniques as feature-based modelling and clustering-based modelling.…”
Section: Related Workmentioning
confidence: 99%
“…An increase in the number of customers who stay this can happen if customers are satisfied with the service facilities offered by the company. Services that do not meet the quality will be very easily abandon and eventually the customer will switch to another company (Yakut, Turkoglu, and Yakut, 2015;Dhandayudam and Krishnamurthi, 2013;Salajegheh, 2016;Li, Tang, Luo, and Xu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Where the Rough Set method can classify the data and is quite effective in the search knowledge. The resulting General Rule will depict which of these four dimensions most dominant affects customer satisfaction, so that the company can manage the strategy in creating customer satisfaction in the future (Stefanowski, 1998;Yakut et al, 2015;Jiang, Kwong, Law, and Ip, 2013).…”
Section: Introductionmentioning
confidence: 99%